PENGOLAHAN DAN PEMANFAATAN AIR LIMBAH INDUSTRI BIODIESEL - Mulyanto, Adi (BPPT)
As a tropical country, the availability of biomass is very abundant in Indonesia. Biomass is a source for renewable energy. One of the renewable energy is biodiesel. Biodiesel is produced by trans-esterifi cation of oil/fat. During the process, biodiesel industry produces either wastewater and/or solid waste. The wastes should be treated carefully. The wastes from biodiesel industry are categorized as organic wastes. Therefore, the treatment and utilization of such wastes is done biologically. The wastewater will be treated through in series of anaerobic, aerobic process and artifi cial wetland. Gas resulted from the stripping process in aerobic lagoon will be treated by using biofi lter. The solid waste will be utilized for producing compost by wind row composting. Wastewater from biodiesel industry contains high organic matter. The Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD) are 21.300 mg/L and 6.300 mg/L. Therefore, during treatment the process should be carefully handled. The quality of treated wastewater will be improved by treating it in an artifi cial wetland. When the treated wastewater has a positive impact towards the plant growth in the artifi cial wetland, then the treated wastewater will be utilized for liquid fertilizer by adding the macro and micro nutrient such as N, P, K, Ca, Mg, Mn, Co,Mo, S, and so forth. The prototype of wastewater treatment facility has been built in PUSPIPTEK Serpong with the capacity of 2.5 m3 of wastewater/day. The anaerobic process is established in an anaerobic digester (fi xed bed). The bed used is made of plastic. The aerobic digester is an activated sludge. Therefore, side products from this activity are biogas, compost and liquid fertilizer.Key words: fixed bed digester, activated sludge, biofi lter, compost, artifi cial wetland.